KKN TEMATIK COVID-19 DI PASAR MAJAPAHIT DESA UMBULHARJO KECAMATAN CANGKRINGAN SLEMAN, MTS Bima BHAKTI PERTIWI SLEMAN DAN UNIVERSITAS COKROAMINOTO YOGYAKARTA - Kusumawati, Intan; Oktavan, Reyhan; Anggita, Dea; Sakty, Bima; Sulistyo, Shanni (Gemi: Jurnal Penelitian dan Pengabdian, 2021)
The impact of the corona virus (Covid-19) outbreak on the tourism industry, especially Indonesia, is certainly very influential. From 2020 to 2021 a number of cancellations of tourist arrivals have occurred since the virus outbreak was announced. The plane seats are empty, as well as hotels, cruise operators, and other business potentials. As an illustration, the realization of foreign tourist visits during 2019 reached 16.3 million from the target of 18 million. In the tourism sector, tourist arrivals, which are currently the second largest in Yogyakarta, are estimated to decline. The same applies to the investment and trade sectors. In recent years, the investment value has continued to increase. It will even become the second largest in 2021. Therefore, it is necessary to have adequate facilities to support the tourism sector in Indonesia during this Covid-19 period. One of them is Majapahit Market which is located in Umbulharjo village, Cangkringan sub-district, Sleman district. The lack of facilities to support health protocols, guides to tourist attractions, as well as tourist attractions that are still relatively simple have made the Majapahit Market experience a significant decline in tourists. In addition to the PPKM carried out by the government, the Majapahit Market should have facilities that support during this Covid-19 period. In addition to the tourism sector, health protocol facilities in some remote educational places also need improvement. Especially on the lack of knowledge of students about the corona virus, as well as how to carry out learning activities with good and correct health protocols. In addition to remote educational places, several educational places in the city also need improvement during this Covid-19 period. One of them is Cokroaminoto University, Yogyakarta. Based on these problems, the authors carry out community service through UCY Thematic Real Work Lecture (KKN) activities in the Covid-19 era. The activity has been carried out by supporting the community by making adequate facilities in the Covid-19 era, as well as providing education, distributing masks, as well as food assistance to MTs Bima Bhakti Pertiwi students who are currently carrying out offline learning activities, and providing assistance for human resources. to the campus to make improvements during this Covid-19 period.